A synergistic optical strategy for enhanced deep-tumor penetration and therapy in the second near-infrared window. Issue 11 (28th August 2020) - Wu, Di; Chen, Xiaohong; Zhou, Jiajing; Chen, Yuxuan; Wan, Tao; Wang, Yi; Lin, Aifu; Ruan, Yeping; Chen, Zhong; Song, Xiangrong; Fang, Wenjun; Duan, Hongwei; et al.
Abstract : A mesoporous core–shell nanohybrid allows delivery of thermophilic enzymes for stromal depletion and high photothermal conversion efficiency for tumor therapy. Abstract : Dense tumor stroma can severely restrict the ability of therapeutic drugs to penetrate into the deep tissue of solid tumors, and thereby inhibit the therapeutic efficacy of cancer nanomedicines. To address this issue, we have developed a synergistic optical strategy for deep-tumor penetration, in which thermophilic enzymes that can deplete tumor stroma are loaded and delivered by mesoporous polydopamine-coated plasmonic nanorods (termed AuNR@mPDA). Due to its high efficiency of photothermal conversion (56.5%) in the second near-infrared (NIR-II) window, AuNR@mPDA can activate thermophilic enzymes to enable on-demand enzymatic depletion of the tumor stroma, thus greatly promoting deep-tumor penetration of AuNR@mPDA. The excellent ability of NIR-II light to penetrate tissue is also crucial to facilitate photothermal therapy in the deep tissue of tumors to enhance in vivo therapeutic efficacy. The current NIR-II optical strategy for the synergistic enzymatic depletion of tumor stroma and photothermal therapy in deep tissue opens a promising avenue for effective treatment of solid tumors.